Reliability and validity of the Turkish version of the prejudice toward people with mental illness scale - Şahin Bayındır, Gizem; Atay, Nuvit; Buzlu, Sevim; Yavaş, Gökçe Çiçek (Kare Publishing, 2023)
Objectives: This study was conducted to assess the validity–reliability and psychometric properties of the Turkish version of the Prejudice toward People with Mental Illness scale. Methods: This was a methodological study conducted between June 1, 2021, and September 1, 2021. The sample of this study consisted of 297 people who were registered at a family health center in Gaziosmanpaşa. The personal information form consisted of 17 questions. It had eight sociodemographic characteristics questions and nine situations participants might find themselves in with people with mental illness. In the data analysis, descriptive statistics, confirmatory factor analysis, item–total correlation, test–retest correlation, Pearson correlation, and Cronbach’s alpha coefficient were used. According to experts’ opinions, the content validity index of the items was 0.97. Results: As a result of confirmatory factor analysis, it was determined that the scale had a four-factor structure and consisted of 19 items. The item–total correlations of the Turkish version of the scale ranged from r=0.30 to r=0.68. The total Cronbach’s alpha coefficient of the scale was found to be 0.86. Test–retest correlations were found to be statistically significant for the total scale and subscales (r=0.48; p<0.01). Conclusion: The Turkish version of the Prejudice toward People with Mental Illness scale is a valid and reliable mea-surement tool that can be used in the evaluation of prejudice toward people with mental illness in the Turkish commu-nity. This scale is also suggested to be used for assessing the efficacy of interventions to reduce public prejudice toward people with mental illness.
Keywords: Mental disorders; Prejudice; Reliability; Validity